FOSTERING CREATIVITY IN CHILDREN: BUILDING THE FOUNDATIONS OF ENTREPRENEURIAL CHARACTERISTICSFOSTERING CREATIVITY IN CHILDREN: BUILDING THE FOUNDATIONS OF ENTREPRENEURIAL CHARACTERISTICS - Keni , Keni; Soelaiman, Lydiawati; Kristanto, Harry; Buana, Salsabila Ayunda Martsa; Leviani, Marissa; Aryon, Debora Christina (Graduate Program of Universitas Tarumanagara, 2024)
The cultivation of an entrepreneurial mindset needs to be nurtured from an early age so that children always think and act entrepreneurially in their daily lives. Building an entrepreneurial spirit is not just about educating children to become entrepreneurs, but also about developing character traits that draw strength from entrepreneurial elements, such as maintaining self-quality to work hard, taking risks, perseverance, being honest, and being creativity. The activity was designed to relevant with students’ learning activities and to have educational, creative, and enjoyable values. The method used to deliver this program involved seminars and workshop on painting tote bag. Participants responded positively to this activity both in the seminar and creativity workshop sessions. It is hoped that through this activity, students' creativity and entrepreneurial spirit will be further honed.